Advances in Social Robotics: A Brief Review of Recent Contributions and Innovations - Romulo, C. S. Thaymara; Boscatti, Lucas P.; Faria, W. S. C. Rejane; Brandão, Alexandre S. (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2023)
This paper presents a review in the field of social robotics over the past five years. With robots becoming increasingly integrated as task assistants, it is imperative to gain a thorough understanding of the existing research landscape before embarking on new developments. The study specifically focuses on two pivotal aspects that drive the progress of social robotics: research innovations and the acceptance of robots by humans. The review identifies and analyzes three primary categories derived from the research findings: device enhancements, human perception, and social impact. Notably, the investigation underscores the domain of assistive robotics, in healthcare applications, including promoting independence among the elderly and facilitating interventions for children with Autism Spectrum Disorder (ASD). Furthermore, the paper emphasizes the critical consideration of robot acceptance, as it is contingent upon factors such as functionality and appearance. Consequently, a comprehensive understanding of these factors is crucial for effectively addressing the specific needs and requirements of the target audience. In summary, this review provides valuable insights into the recent contributions and innovations that have shaped the rapidly evolving landscape of social robotics.